2019
DOI: 10.1002/asna.201913548
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a compressive velocity pulse on a collapsing turbulent clump

Abstract: High‐resolution hydrodynamical simulations are presented to follow the gravitational collapse of a uniform turbulent clump, upon which a purely radial compressive velocity pulse is activated in the midst of the evolution of the clump, when its turbulent state has been fully developed. The shape of the velocity pulse is determined basically by two free parameters: the velocity V0 and the initial radial position r0. In the present paper, models are considered in which the velocity V0 takes the values 2, 5, 10, 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Despite of this, when we calculated the α f and β f values we observe that some binary fragments do show a clear tendency to virialize, as it can be appreciated in Fig.31. We emphasize that a similar conclusion can be drawn from the calculation of Arreaga et al (2008), where plots of the α f and β f time evolution were also presented. On the contrary, for the central primaries, we do not observe any trend to approach the virial line; see Fig.33.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Despite of this, when we calculated the α f and β f values we observe that some binary fragments do show a clear tendency to virialize, as it can be appreciated in Fig.31. We emphasize that a similar conclusion can be drawn from the calculation of Arreaga et al (2008), where plots of the α f and β f time evolution were also presented. On the contrary, for the central primaries, we do not observe any trend to approach the virial line; see Fig.33.…”
Section: Discussionsupporting
confidence: 76%
“…This mass perturbation scheme was successfully applied in many papers on collapse; see for instance Arreaga et al (2007), Arreaga et al (2008), Arreaga and Klapp (2010), and notably Springel (2005), when the Gadget2 code was proven, among other tests, with the calculation of the isothermal collapse, where the unequal mass particles method was validated. et al (1997) demonstrated the need of fulfill appropriate spatial resolution requirements in order to avoid the occurrence of artificial fragmentation in a collapse simulation.…”
Section: The Mass Perturbationmentioning
confidence: 99%